TANGGUNG JAWAB HUKUM PEMERINTAH TERHADAP KERUSAKAN JALAN YANG MENGAKIBATKAN KECELAKAAN - Siregar, Solhani Guntur; Fahmi; Yetti (The Juris, 2024)
The purpose of this study is to analyze the Regulation of Government Legal Responsibility for Road Damage Resulting in Accidents Based on Law Number 22 of 2009 Concerning Traffic and Road Transportation, To analyze the Government's Legal Responsibility for Road Damage Resulting in Accidents Based on Law Number 22 of 2009 Concerning Traffic and Road Transportation. The method used is normative legal research, namely research based on applicable legal principles, in this case the research was conducted on the Government's Legal Responsibility for Road Damage Resulting in Accidents Based on Law Number 22 of 2009 Concerning Traffic and Road Transportation. Based on the results of the study, it is known that the Regulation of Government Legal Responsibility for Road Damage Resulting in Accidents Based on Law Number 22 of 2009 Concerning Traffic and Road Transportation that the Government is required to carry out road maintenance and repairs, provide warning signs during the repair process, and can be held legally accountable if proven negligent. However, the main challenge lies in the implementation in the field, where further efforts are still needed to ensure the safety and comfort of road users. Thus, it is expected that the government can be more serious in carrying out its responsibilities to reduce the risk of accidents due to road damage. Government's Legal Responsibility for Road Damage Causing Accidents Based on Law Number 22 of 2009 concerning Traffic and Road Transportation, the Government is required to carry out road maintenance and repairs, provide warning signs during the repair process, and can be held legally accountable if proven negligent. However, the main challenge is ensuring effective implementation in the field to reduce the risk of accidents due to road damage. It is expected that with the increased seriousness of the government in carrying out its responsibilities, the safety and comfort of road users can be more assured.